Pengaruh Likuiditas dan Leverage terhadap Kebijakan Dividen dengan Firm Size sebagai Variabel Mediasi pada Perusahaan Sektor Infrastructure, Utilities and Transportation di Bei Periode 2014-2018 - Lisfi Dita Anggraini (UNESA In Collaboration With APSMBI (Aliansi Program Studi dan Bisnis Indonesia), 2022)
The movement of the average value of the dividend policy from 2014 to 2018 experienced fluctuating in its growth. Infrastructure, utilities and transportation sectors experienced a significant increase each year compared to the others. Based on bps data, Gross Domestic Product (GDP) fluctuated. This study aims to determine the effect of liquidity and leverage on dividend policy with firm size as a mediating variable in the infrastructure, utilities and transportation sectors listed on the IDX in 2014-2018. This study uses causal research with a quantitative approach. The population of this study consisted of 74 companies with a sample of 10 companies using the purposive sampling technique. The data analysis method used in this study uses path analysis with SmartPLS 3.0 software. This study revealed that liquidity has a positive effect on dividends, which leads the company to have the ability to settle its short term with current assets so that the cash position is more robust and increases the ability to pay a dividend. Liquidity hurts size because the company cannot always meet its short-term obligations in carrying out its activities properly to earn profits and increase its assets. Leverage and firm size do not affect dividend policy. The leverage does not affect the firm size. It means the relationship cannot mediate that firm size between liquidity and leverage on dividend policy. The firm can use the results of this study to determine the amount of dividend policy distributed to shareholders.